A STUDY OF KNOWLEDGE, ATTITUDES, AND PRACTICES TOWARDS TOBACCO CESSATION SERVICES (TCS) AMONG CLINICIANS IN A TERTIARY CARE TEACHING HOSPITAL: Life Science-Medicine - SAMPATH, HARSHAVARDHAN; SHARMA, DIVIJ; SOOHINDA, GEETA (International Journal of Life Science and Pharma Research, 2019)
Tobacco consumption is a leading cause of death and disability globally. Though legislation and policies have been successful in bringing down the number of new tobacco users, it is the responsibility of health professionals to address the millions of current tobacco users in India by providing Tobacco Cessation Services (TCS). The present study aimed to understand the knowledge, attitudes, barriers, current practices, and motivation to learn about TCS among clinicians of a tertiary care teaching hospital. This was a cross-sectional, questionnaire-based study that included all clinicians who gave their written consent. Of the 90 clinicians who participated in the study, 74.4% did not have formal training in TCS. Doctor’s knowledge of the harmful effects and treatment modalities were better than their knowledge of the epidemiology of tobacco use. Most doctors had positive attitudes towards TCS. Common barriers cited were the lack of referral TCS (53.3%), unmotivated patients (40%), lack of skills (35.6%), and time constraints (34.4%). Doctors enquired about tobacco use 31.3% of the time, assessing it routinely only in patients with tobacco-related complications (75%). Anticraving medications (25.6%) and nicotine replacement therapy (37.8%) were prescribed to patients infrequently. 33.3% of the doctors arranged for follow-up visits to inquire about the success of TCS. Only 32.2% of patients were referred to psychiatric services. 41.1% (counseling) and 47.8% (pharmacotherapy) of the doctors were very interested to learn about TCS. There is a dire need to train clinicians to offer brief tobacco cessation interventions and to establish specialized TCS in hospitals for referral of patients.